2017
DOI: 10.1016/j.schres.2017.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Morphological brain changes associated with negative symptoms in patients with 22q11.2 Deletion Syndrome

Abstract: Approximately 30% of individuals with 22q11.2 Deletion Syndrome (22q11DS) develop schizophrenia during adolescence/early adulthood, making this syndrome a model for the disorder. Furthermore, negative symptoms exist in up to 80% of patients diagnosed with 22q11DS. The present study aims to uncover morphological brain alterations associated with negative symptoms in a cohort of patients with 22q11DS who are at-risk for developing schizophrenia. A total of 71 patients with 22q11DS aged 12 to 35 (54% females) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…The second hypothesis is that altered gyrification is associated to negative symptoms rather than positive symptoms. In our recent publication (Mihailov et al 2017), we indeed showed reduced gyrification in patients with 22q11DS with high negative symptoms, as compared to patients with low symptoms scores. However, this hypothesis needs to be further confirmed by investigations directly comparing gyrification between subgroups of patients expressing preferentially high positive or high negative symptoms.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The second hypothesis is that altered gyrification is associated to negative symptoms rather than positive symptoms. In our recent publication (Mihailov et al 2017), we indeed showed reduced gyrification in patients with 22q11DS with high negative symptoms, as compared to patients with low symptoms scores. However, this hypothesis needs to be further confirmed by investigations directly comparing gyrification between subgroups of patients expressing preferentially high positive or high negative symptoms.…”
Section: Discussionsupporting
confidence: 70%
“…Second, when comparing patients with 22q11DS to healthy controls, a number of factors can account for the differences observed between the groups, such as the cognitive impairments and the lower IQ. The studies conducted to date showed alterations in cortical thickness, volume and gyrification in association to more severe positive symptoms (Schaer et al 2009; Gothelf et al 2011; Kates et al 2011; Jalbrzikowski et al 2013; Schmitt et al 2015; Bakker et al 2016), and reduced gyrification in association to higher negative symptoms (Mihailov et al 2017) in patients with 22q11DS. Furthermore, longitudinal investigations revealed altered developmental trajectories associated with higher positive symptoms severity in patients with the syndrome (Radoeva et al 2017; Ramanathan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While some CSM features, i.e. gray matter volume, are sensitive to antipsychotic medication (53)(54)(55)(56)(57)(58), it remains unclear if gyrification is stable across treatment. The present study only included a small number of the CHR participants treated with antipsychotic medications (n=8) and did not find a significant effect of medication.…”
Section: Discussionmentioning
confidence: 99%
“…These deletions are also found to be linked with other neuropsychiatric disorders, including DiGeorge Syndrome, conotruncal anomaly face syndrome, velocardiofacial syndrome, intellectual disability, and schizophrenia 60,61 . 22q11.2 deletion in patients having high-risk negative symptoms at risk of developing schizophrenia showed decreased gyrification mainly in the medial occipital and temporal regions, involved in social cognition and early visual processing 62 . Another study reported increased cortical thickness in the frontal lobe, cerebral cortex, and superior parietal lobes and decreased cortical thickness in the regions of superior temporal gyrus and posterior cingulate cortex in patients with 22q11.2 deletion syndrome 63 .…”
Section: Clinical Studiesmentioning
confidence: 95%